2019
DOI: 10.1039/c9nj01818b
|View full text |Cite
|
Sign up to set email alerts
|

A ligand-anchored optical composite material for efficient vanadium(ii) adsorption and detection in wastewater

Abstract: A ligand-anchored composite material was prepared for vanadium (V(ii)) ion capturing. The pH was found to be a key factor in both detection and removal operations. The composite material exhibited the high adsorption capacity of 492.61 mg g−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(10 citation statements)
references
References 122 publications
0
10
0
Order By: Relevance
“…Depending on the concentration and pH value of the solution, vanadium forms more than 11 species of oxyanion compounds in an aqueous solution [ 8 ]. In the low pH range (<3), V(V) is present in the solution mainly as a cation VO 2 + .…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the concentration and pH value of the solution, vanadium forms more than 11 species of oxyanion compounds in an aqueous solution [ 8 ]. In the low pH range (<3), V(V) is present in the solution mainly as a cation VO 2 + .…”
Section: Introductionmentioning
confidence: 99%
“…The mesoporous silica attracted attention because of its specific surface functionality, porous wall structure, biocompatibility, and hydrophilic design [13–22] . MSNSs (mesoporous silica nanospheres) were created and used as a scaffold for accommodating new ion chromophores in this study (Phimhb).…”
Section: Resultsmentioning
confidence: 99%
“…Many papers showed that the use of nanomaterials as a scaffold for immobilization of the reagents enhances their selectivity and sensitivity [13–22] . From this point of view, we tried to far away from the routine work and make a chemosensor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption capacity of the new composite was found to be 492.61 mg g -1 . The composite materials also exhibit the property of selectivity and sensitivity for the capture of vanadium ions from waste water [56].…”
Section: Ligand Based Adsorption Of Metal Ionsmentioning
confidence: 99%